2018
DOI: 10.1002/clc.23066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticoagulation use and subsequent stroke in patients with atrial fibrillation after empiric surgical left atrial appendage closure: A retrospective case‐control study

Abstract: Background Surgical exclusion of the left atrial appendage (LAA) can be performed at the time of cardiac operation as a potential modality to decrease cardioembolic risk attributable to atrial fibrillation (AF), but it remains unclear if this decreases stroke incidence. Furthermore, it is not known whether LAA exclusion impacts the decision to discontinue anticoagulation impacting subsequent stroke risk. Hypothesis LAA exclusion does not significantly alter subsequent anticoagulation use or stroke incidence. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…A similar pattern in patients' characteristics between the LAA exclusion and nonexclusion groups in the AF subgroup to the total population was seen ( This study showed that exclusion of LAA by closing it using a double-layer suture during MVR reduced the incidence of ischemic stroke during hospitalization, particulary in patients with AF. It is consistent with several other observational studies [8][9][10][11][12][13][14][15] where LAA exclusion has been recognized as a protective factor for different types of patients undergoing cardiac surgery ( Table 5).…”
Section: Surgical Techniquesupporting
confidence: 92%
“…A similar pattern in patients' characteristics between the LAA exclusion and nonexclusion groups in the AF subgroup to the total population was seen ( This study showed that exclusion of LAA by closing it using a double-layer suture during MVR reduced the incidence of ischemic stroke during hospitalization, particulary in patients with AF. It is consistent with several other observational studies [8][9][10][11][12][13][14][15] where LAA exclusion has been recognized as a protective factor for different types of patients undergoing cardiac surgery ( Table 5).…”
Section: Surgical Techniquesupporting
confidence: 92%
“…PRISMA flow diagram presenting the study selection process is available in Figure 1 . Electronic search returned 25 studies (N = 660 [158 patients]) 8 , 9 , 10 , 11 , 12 , 13 , 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , E1 , E9 to be included in the systematic review. Seven studies were RCTs 10 , 15 , 18 , 33 , 34 , E3 , E4 ; of the remaining, 8 9 , 12 , 29 , 32 , 35 , E2 , E7 provided adjusted estimates.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of AF varied across studies and ranged from 0% 15 to 100%. 8 , 10 , 11 , 13 , 28 , 29 , 30 , 31 , 35 , E2 , E4 , E5 , E7 Yao and colleagues 9 provide outcome data for patients with AF and those without separately. In studies labeled as predominantly AF, 99.7% of patients had preoperative AF.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] However, a recent study from the Mayo Clinic [ 14 ] using a propensity-matched analysis did not demonstrate that SLAAO significantly influenced the risk of stroke or long-term mortality. Furthermore, Johnsrud et al , [ 15 ] also from the Mayo Clinic, published a PSM analysis and stated that SLAAO did not appear to reduce the incidence of early or late stroke.…”
Section: Discussionmentioning
confidence: 99%